Systematic Review of Storytelling Analytics for Strengthening Brand Equity in Global Markets (International Journal of Scientific Research in Science and Technology, 2024)
This systematic review explores the role of storytelling analytics in enhancing brand equity across global markets. As digital transformation reshapes how brands engage with consumers, storytelling has emerged as a key strategy for building emotional connections and fostering brand loyalty. However, the integration of data analytics into storytelling practices is still an evolving field. This review synthesizes existing literature on storytelling analytics, focusing on how data-driven insights can optimize brand narratives, improve consumer engagement, and strengthen brand equity. By examining studies from diverse industries and geographical contexts, this review identifies key methodologies, tools, and techniques used to analyze and measure the effectiveness of storytelling in branding efforts. It highlights how analytics can be used to personalize stories, predict consumer responses, and track the impact of storytelling on brand perception, loyalty, and overall equity. The review also discusses the challenges of implementing storytelling analytics, such as data privacy concerns, cultural differences, and the need for cross-disciplinary collaboration. Furthermore, it explores the implications for global market strategies, emphasizing the importance of adapting storytelling to diverse cultural contexts while leveraging data analytics to maintain consistency and authenticity. The findings indicate that storytelling analytics can significantly influence brand equity, but it requires a strategic approach that combines creative storytelling with robust data analysis. In conclusion, this review provides insights into the growing importance of storytelling analytics in global branding and offers recommendations for brands seeking to enhance their equity in an increasingly competitive and data-driven marketplace.